Analysis of posyandu cadre duties in implementing the stunting prevention program - Utari Ariyanti; Selvia Yolanda Dalimunthe; Yessica Hotmaida Tarihoran (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Stunting is a chronic nutritional problem that has a serious impact on children's growth and development, particularly during the first 1,000 days of life. Community-based health efforts are essential in preventing stunting, with Posyandu cadres playing a key role at the grassroots level. Purpose: to analyze the roles and duties of Posyandu cadres in implementing stunting prevention programs, Method: This research employed a quantitative design using a Chi-Square analysis approach to examine the relationship between the roles and duties of Posyandu cadres and stunting prevention efforts. Results: The results showed a significant relationship between all roles and duties of Posyandu cadres and stunting prevention efforts, as indicated by P-values < α for all analyzed variables. These findings are supported by secondary data and previous studies demonstrating that active cadre involvement in education, monitoring, and nutritional interventions contributes substantially to reducing stunting prevalence. Conclusion: Posyandu cadres have a strategic and significant role in stunting prevention within the community through education, monitoring, and direct nutritional interventions.